First person - Zhaoyang Liu (The Company of Biologists, 2019)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Zhaoyang Liu is first author on 'Regulation of terminal hypertrophic chondrocyte differentiation in Prmt5 mutant mice modeling infantile idiopathic scoliosis', published in DMM. Zhaoyang is a postdoctoral fellow in the lab of Ryan Gray at The University of Texas at Austin, Austin, TX, USA, investigating mechanisms of cartilage development and musculoskeletal-related diseases.